Social Transfers and Child Poverty in European Countries: Pro-poor Targeting or Pro-child Targeting? - Bárcena-Martín, Elena María; Blanco-Arana, María del Carmen; Pérez-Moreno, Salvador Jesús (Cambridge University Press, 2018)
Children are generally at a higher risk of poverty than the population as a whole, although the mechanisms that lead to their socio-economic vulnerability vary widely across European countries. This paper aims to further our understanding of to what extent cross-country variations in child poverty risk are associated with different ways of social transfer targeting: pro-poor versus pro-child targeting. In particular, we address the potential impact on child poverty of countries’ intent to target transfers at lower incomes and children across30 European countries. Using a multilevel framework, we find that not only the size of the transfer system, but also the form of targeting matters in reducing child poverty. Specifically, the countries’ intent to target children matters even more than their intent to target lower incomes, in terms of reducing child poverty. Moreover, the prevalence of multi-generational households in a country seems to be associated with an attempt to protect against child poverty in countries with lower levels of pro-child targeting.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/1988
Keywords: Niños pobres - Unión Europea; Econometría - Análisis; European countries; Social transfers; Child poverty; Pro-poor targeting; Pro-child targeting